alpha-Amylase immobilization on functionalized nano CaCO3 by covalent attachment - KAHRAMAN, MEMET VEZİR; DEMİR, SERAP (WILEY-V C H VERLAG GMBH, 2012)
In this study, a-amylase was immobilized on glutaraldehyde activated silanized calcium carbonate nanoparticles by a using covalent binding method. The surface modified nano calcium carbonate (CaCO3) were characterized using FTIR and SEM. Immobilization yield was found as 199.43 mg/g of calcium carbonate nanoparticles. The maximum activity was observed at pH 6.5. The immobilized enzyme had a higher activity at elevated temperature (5090 degrees C) than the free one. Reuse studies demonstrated that the immobilized enzyme could reuse 25 times while retaining 18.2% of its activity. Free enzyme lost its activity completely within 15 days. Vmax values for the free and immobilized enzymes were calculated as 10 and 0.35 mg/mL/min, respectively.
Keywords: a-Amylase; Covalent Immobilization; Enzyme; Glutaraldehyde; Nano CaCO3; ENZYME; PERFORMANCE; STABILITY; CHITOSAN; SURFACE; MATRIX; TOOL